7.3 dB Polarization Squeezing Using Kerr Effect in Fibers - Kalinin, Nikolay; Leuchs, Gerd; Sánchez-Soto, Luis L.; Andrianov, Alexey V. (Quantum 2.0 in Proceedings Quantum 2.0 Conference and Exhibition, 2024)
We report on a record 7.3 dB polarization squeezing generation using Kerr effect in a polarization-maintaining fiber and propose a way to apply such squeezed states for sensitivity enhancements in Michelson-like interferometers.
CRIS-Team Scopus Importer:2024-11-01